2020
DOI: 10.3390/ijms21051585
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implications of Quercetin and its Derivatives in Cardioprotection

Abstract: Quercetin (QCT) is a natural polyphenolic compound enriched in human food, mainly in vegetables, fruits and berries. QCT and its main derivatives, such as rhamnetin, rutin, hyperoside, etc., have been documented to possess many beneficial effects in the human body including their positive effects in the cardiovascular system. However, clinical implications of QCT and its derivatives are still rare. In the current paper we provide a complex picture of the most recent knowledge on the effects of QCT and its deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 111 publications
1
73
0
Order By: Relevance
“…Both Caco-2 cells treated with isoquercitrin alone accumulated both quercetin and isoquercitrin within an hour, suggesting that isoquercitrin is readily metabolized to quercetin by cellular glucosidases [ 57 ]. Dietary flavonoids undergo diverse metabolism in the intestinal tract by enzymes such as lactase-phlorizin hydrolase and cytosolic glucosidases as well as microbiota [ 52 , 53 , 59 ]. This metabolic transformation may influence the absorption and bioavailability of individual quercetin derivatives in a more intensive and complicated manner, in plant extracts composed of diverse flavonoids [ 52 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Caco-2 cells treated with isoquercitrin alone accumulated both quercetin and isoquercitrin within an hour, suggesting that isoquercitrin is readily metabolized to quercetin by cellular glucosidases [ 57 ]. Dietary flavonoids undergo diverse metabolism in the intestinal tract by enzymes such as lactase-phlorizin hydrolase and cytosolic glucosidases as well as microbiota [ 52 , 53 , 59 ]. This metabolic transformation may influence the absorption and bioavailability of individual quercetin derivatives in a more intensive and complicated manner, in plant extracts composed of diverse flavonoids [ 52 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are important for human health because of their strong antioxidant and anticancer activities [ 54 , 55 , 56 ]. The consumption of products rich in quercetin and its glycosides reduces the risk of cardiovascular [ 57 , 58 ] and neurodegenerative diseases [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin, a flavonoid, is a potent antioxidant found in common medicinal herbs and possesses a wide spectrum of biologic activities [ 36 ]. It also has antioxidant, hypoglycemic, hypolipidemic, tumor suppression, and anti-inflammatory effects [ 37 , 38 ]. One study showed that quercetin liposome or free quercetin could prevent weight loss, decrease kidney hypertrophy index, decrease blood glucose level, and decrease 24-hour urine protein levels in diabetic nephropathy model rats [ 39 ].…”
Section: Discussionmentioning
confidence: 99%